ANALISIS ISI BUKU SISWA BAHASA ARAB MADRASAH TSANAWIYAH KURIKULUM 2013 - Nunung Kurniawati (Muróbbî: Jurnal Ilmu Pendidikan, 2019)
Learning materials are one element of learning and this is the task of getting teachers' attention so that students can learn the things required in achieving learning goals. This study aims to find the compatibility of the textbook with the theory of the drafting of books to learn Arabic for non-native speakers. This study uses a content analysis method that is a research method used to draw conclusions that can be re-examined based on facts by paying attention to the empirically oriented context of interpretation and explanation of the true symptoms and the purpose of the prediction .from the previous statements the results showed: 1) In the preparation of the book, the degree of compatibility reached 20%; 2) In the normative aspect of cognitive and cultural content, the degree of compatibility reached 91%. 3) In terms of language skills, the degree of compatibility reached 84%. 4) On the vocabulary side, the score reached 91%. 5) On the side of grammatical structures, the degree of compatibility reached 89%. 7) In terms of learning mode, the degree of compatibility reached 92%. 8) In the book output side, the degree of compatibility reached 75.%. 9) In general aspects, the degree of compatibility reached 81%. 10) In the material accompanying the book, the degree ofcompatibility reached 50%.